2021
DOI: 10.1186/s40662-020-00224-0
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal blood perfusion as a potential “rapid predictive index” for myopia development and progression

Abstract: Myopia is the leading cause of visual impairment worldwide. The lack of a “rapid predictive index” for myopia development and progression hinders the clinic management and prevention of myopia. This article reviews the studies describing changes that occur in the choroid during myopia development and proposes that it is possible to detect myopia development at an earlier stage than is currently possible in a clinical setting using choroidal blood perfusion as a “rapid predictive index” of myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Our study revealed that CCF remained stable regardless of the treatment or observation time, indicating that the choroidal capillary layer was not affected by atropine 0.01%. Given a recently proposed hypothesis that altered choroidal vasculature and decreased choroidal blood flow may lead to scleral hypoxia which then triggers scleral remodeling and myopia development [72], more evidence is required to investigate the changes in choroidal structure and function and its relationship with myopia onset and progression [73].…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that CCF remained stable regardless of the treatment or observation time, indicating that the choroidal capillary layer was not affected by atropine 0.01%. Given a recently proposed hypothesis that altered choroidal vasculature and decreased choroidal blood flow may lead to scleral hypoxia which then triggers scleral remodeling and myopia development [72], more evidence is required to investigate the changes in choroidal structure and function and its relationship with myopia onset and progression [73].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a detailed, comprehensive assessment of the choroidal vasculature and choriocapillaris perfusion might be more informative. 46,47 Studies with animal models in which myopia is induced by unilateral manipulation of visual inputs have established that alteration in ChT is an early sign of vision-driven changes in ocular growth and myopia development. [13][14][15] The ChT responds to visual stimuli in a bidirectional, rapid, and regionally selective manner.…”
Section: Discussionmentioning
confidence: 99%
“…The nutrient supply of the choroid mainly comes from the short-posterior ciliary artery. As one of the most highly vascularized tissues of the body, the choroid accounts for 65% of the blood supply within the eye; hence, it is reasonable to assume that the progression of pathological myopia is linked to the structural and functional alterations of the choroid (5,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%